2012
DOI: 10.1258/vasc.2011.cr0299
|View full text |Cite
|
Sign up to set email alerts
|

Aortic graft infection and mycotic aneurysm with Streptococcus equi zooepidemicus: two cases with favorable outcome of antibiotic treatment

Abstract: Infections with Streptococcus equi zooepidemicus are rare and are associated with contact with animals or animal products. There are very few reports about infected vascular grafts or aneurysms with this etiology. We present two patients. The first is a 77-year-old man with an infected bifurcated graft four years after an open operation for an abdominal aortic aneurysm (AAA). The second is a 72-year-old man with a symptomatic mycotic AAA, treated with endovascular aneurysm repair. Both received prolonged treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Therefore, our intent is for the patient to remain on lifelong antibiotic prophylaxis. S. equi has been reported to cause secondary infections of atherosclerotic abdominal aorta aneurysms and vascular grafts [18,19]. Our report demonstrates that the organism can cause mycotic aneurysms as well.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, our intent is for the patient to remain on lifelong antibiotic prophylaxis. S. equi has been reported to cause secondary infections of atherosclerotic abdominal aorta aneurysms and vascular grafts [18,19]. Our report demonstrates that the organism can cause mycotic aneurysms as well.…”
Section: Discussionsupporting
confidence: 55%
“…The efficacy of aortic stent-graft deployment in the management of mycotic abdominal aortic aneurysms as an alternative strategy has been described by Kan et al 24 Kan et al 25 also mentioned from a literature review, they performed that the 30-day survival rate was 89.6%, and the 2-year survival rate was 82.2%. Altreuther et al 26 reported 2 cases of mycotic aneurysms with streptococcus equi zooepidemicus treated with EVAR and prolonged antibiotic administration. A European multicenter analysis of 123 patients treated for mycotic aortic aneurysms with EVAR demonstrated the feasibility of this approach, with 91% survival at 30 days, whereas it comprised a durable option.…”
Section: Discussionmentioning
confidence: 99%
“…With time, a graft biofilm infection can evolve to a more virulent infectious process, with superinfection by other bacteria such as methicillin-sensitive S. aureus or MRSA 12. Recent case reports have shown the appearance of unusual etiological agents as Streptococcus equi zooepidemicus in patients who had contact with animals or animal products 24…”
Section: Discussionmentioning
confidence: 99%